2013
DOI: 10.4238/2013.august.29.5
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of leaf extract of Breonadia salicina (Rubeaceae), an endangered medicinal plant of Saudi Arabia

Abstract: ABSTRACT. Wild plants can contain bioactive compounds with potential activity against disease-causing microorganisms. In the Kingdom of Saudi Arabia, there are many plant species that may have antibacterial, antifungal, or antiviral activities, among other properties. We extracted bioactive compounds with methanol as well as with water from leaves of Breonadia salicina, which is an endangered plant found in the wild in Saudi Arabia. These extracts were tested against the bacteria Bacillus subtilis, Pseudomonas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The parsley essential oil in our study showed high bactericidal activity mostly against P. aeruginosa, S. enterica, and S. aureus. These bacteria are common food pathogens and produce a wide variety of toxins (Al-Qurainy et al, 2013). S. aureus -for instance -is heat resistant, can live at low pH with activity in the digestive tract after ingestion, and is a common cause of skin infection and food poisoning (Evenson et al, 1988;AlQurainy et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parsley essential oil in our study showed high bactericidal activity mostly against P. aeruginosa, S. enterica, and S. aureus. These bacteria are common food pathogens and produce a wide variety of toxins (Al-Qurainy et al, 2013). S. aureus -for instance -is heat resistant, can live at low pH with activity in the digestive tract after ingestion, and is a common cause of skin infection and food poisoning (Evenson et al, 1988;AlQurainy et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the antibacterial activity of parsley essential oil -a plant that is widely used as fresh green sprigs to garnish and aromatize foods -could be an alternative to control bacteria during food processing, storage, and/or packing. Moreover, according to Al-Qurainy et al (2013), the use of crude plant extracts and essential oils can be used to reduce the use of synthetic chemical compounds in the preservation of foodstuff. Synthetic food preservatives are effective and inexpensive, but they can be also toxic for animals, the environment, and increase microorganism resistance (Aarestrup, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The high cost of modern medicine and resistance of most organisms to these drugs are on the increase, and this has led to the high interest in medicinal plants. 4 Traditional medicine or ethnobotany is believed to be cheap and can provide novel drug scaffolds for drug discovery. [5][6][7] Breonadia salicina (Rubiaceace) is a monotypic genus of flowering plants.…”
Section: Introductionmentioning
confidence: 99%
“…Many plant families are of current interest in medicinal research. Interestingly, various parts of the plants in the genus Rubiaceae have been reported to have significant antibacterial efficacies [4,5]. For instance, the roots of Catunaregam tomentosa reportedly have antibacterial properties against some Gram positive bacteria [6].…”
Section: Introductionmentioning
confidence: 99%